(untitled) (Third Sector Social Economic Review, 2019)
This study examines how per capita income (PCI) changes in countries with different economic structures affect labor force participation rates (LFPR), which is an expression of people’s desire to work. In the study, panel data is used for two different countries groups consisting of emerging market and OECD countries, covering the years 1990-2015. Panel cointegration test results show a long-term relationship between PCI growth and LFPR in all countries. However, the direction of this relationship is different in OECD and emerging countries. While the increase in PCI in emerging market economies positively affects the women’s and men’s LFPR, this effect is negative in OECD countries. Increases in PCI in all countries keep women in the labor market more than men. In the case of rising PCI, the LFPR of women in emerging market countries increases more than men, while in the OECD countries women’s LFPR decreases less than men’s LFPR.